2020
DOI: 10.1371/journal.pone.0242655
|View full text |Cite
|
Sign up to set email alerts
|

Antibody profiling and prevalence in US patients during the SARS-CoV2 pandemic

Abstract: Background Antibody diagnostics play an important role in disease detection and can potentially aid in monitoring of the immune responses to see if an individual has developed immunity. Developing high throughput diagnostics which does not involve handling of infectious material becomes imperative in the case of pandemics such as the recent outbreak of SARS-CoV2. Methods A protein microarray technology was used to detect the plurality of antibody response to four novel antigens namely S1 glycoprotein, Recept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Data are presented as % (95% confidence levels). A more comprehensive analysis of the sensitivity and specificity of the Vibrant chemiluminescent immunoassay for SARS-CoV-2 has recently been published 26 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data are presented as % (95% confidence levels). A more comprehensive analysis of the sensitivity and specificity of the Vibrant chemiluminescent immunoassay for SARS-CoV-2 has recently been published 26 .…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, we utilized a multiplex serology test for COVID-19 in an otherwise healthy cohort of adults and children in Colorado. Recent results using the same test kit have shown that IgM antibodies against SARS-CoV-2 are generally detectable in blood several days after initial infection, although levels over time are not well characterized 26 . Our results show that IgM levels and IgG levels were both elevated early (0–30 days following symptom onset).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that some participants shielded their answer and submitted samples for analysis without meeting the eligibility criteria; this would have inflated our estimation of seroprevalence in asymptomatic groups, Thirdly, the limited number of non-White, and gender-diverse participants also limited some analyses. Fourthly, while multiple studies have validated DBS sampling for SARS-CoV-2, 46 waning antibodies in asymptomatic individuals could be below the limited of detection of the ELISA assay. Finally, generalizability is limited due to the recruitment of a university-affiliated population in a relatively restricted geographic area.…”
Section: Discussionmentioning
confidence: 99%